A Mixture of Canonical Vine Copula-GARCH Approach for Modeling Dependence of European Electricity Markets: Jiechen Tang, Songsak Sriboonchitta, Xinyu Yuan - Team, Support (Thai Journal of Mathematics, 2014)
This paper employed a mixed Canonical Vine Copula-GARCH ap-proach for modeling the dependence structures of European electricity markets.The electricity spot prices are taken from French, German, Spanish, Dutch, andBritish markets. The empirical result shows that pairwise positive dependencebetween markets is represented in Tree 1, in which there is positive spillover eectbetween the French and the other four markets. Moreover, the French, German,and Dutch markets have strong symmetric tail dependence, which suggests onemarket (one of the French, German, or Dutch markets) experiencing spikes ordrops, conditional on the event that the other two markets are also experiencingspikes or drops. Additionally, we also found that when adding the condition underone or more markets, the relationships of some pairs still had dependence, whilesome other pairs became independent.